Perspektif Demografis dan Perilaku Status Quo Terhadap Perubahan di Perguruan Tinggi: Suatu Tinjauan Keislaman - Fikri, Fikri; Hidayat, Ahmad; Suci, Afred; Raudah, Shalawati Fi (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
Dynamic change has occurred not only in business and governmental organizations but also in higher education. The implications are not merely practical but can also be studied psychologically. This study aimed to examine the impact of status quo behavior on change resistance in private higher education, including observing the role of lecturer demographics, namely gender and lecturing tenure, in the context of status quo and change resistance intensity. Data were collected from 100 lecturers using questionnaires. Hypotheses were tested by employing descriptive statistics, simple linear regression, and Kruskal-Wallis tests. The descriptive test results indicated that lecturers' status quo behavior was relatively moderate with a low level of change resistance. The regression test results proved the positive and significant impact of status quo on the intensity of change resistance. The Kruskal-Wallis test showed no significant difference in status quo behavior and change resistance intensity between male and female lecturers. Meanwhile, in Islamic perspective, positive change is considered the main key to achieving significant progress, improvement, and innovation. Lecturing tenure shows a significant difference in change resistance intensity, even though it is not significantly different in terms of status quo behavior.